Three New Hasubanan Alkaloids from Stephania hernandifolia (Willd.) Walp. Issue 10 (16th October 2013) - Tang, Li‐Jia; Deng, Lu‐Lu; He, Li; Song, Shao‐Hui; Zhang, Jian‐Xin; Hao, Xiao‐Jiang; Zhang, Yuan‐Hu
Abstract Three new hasubanan alkaloids, hernsubanines A–C (1–3, resp.), were isolated from the whole plants of Stephania hernandifolia. Their structures were elucidated on the basis of physical and spectroscopic data. In in vitro tests for cytotoxic activity against two human cancer cell lines, A 549 and K 562, compound 1 did not exhibit any cytotoxicity.